The myth of Sisyphus - Camus, Albert, 1913-1960 (Vintage International : Vintage Books, a division of Penguin Random House LLC, 2018)
One of the most influential works of this century, The Myth of Sisyphus--featured here in a stand-alone edition--is a crucial exposition of existentialist thought. Influenced by works such as Don Juan and the novels of Kafka, these essays begin with a meditation on suicide--the question of living or not living in a universe devoid of order or meaning. With lyric eloquence, Albert Camus brilliantly posits a way out of despair, reaffirming the value of personal existence, and the possibility of life lived with dignity and authenticity. --amazon.com.